The Place of Special Schools in Inclusive Education - Nikolic, Gordana I.; Đorđić, Dejan M.; Kovačević, Jasmina M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The role of schools for the education of students with disabilities is associated with the context of inclusive education in different ways. On the one hand, they are accepted as institutions that, in their full capacity, can and should support education and social inclusion, while another approach considers that further existence of these schools is a reflection of the lack of the inclusion process. The aim of this paper is to determine the role of these schools and the changes that have occurred in their work since 2009, when inclusive education was introduced into the Serbian educational system. The sample covered all 48 schools for the education of students with disabilities on the territory of the Republic of Serbia. For the needs of the research, a questionnaire for collecting data from these schools was prepared at the Institute for the Improvement of Education. The results showed that the network of these institutions has not changed, but that users have changed at all levels of education, since these schools now educate children with several types of disabilities. The number of defectologists is higher in Belgrade and Vojvodina than in the rest of Serbia, (p
Keywords: special schools; inclusive education; outcomes; ecosystem